Young Abe Lincoln the frontier days, 1809-1837 - Harness, Cheryl (Washington, D.C. : National Geographic Society, 2008)
Briefly presents the life of this famous president from his birth until the age of twenty-eight.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes bibliographical references.
Description based on print version record.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Childhood and youth -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; Lincoln, Abraham, -- 1809-1865 -- Childhood and youth; Presidents; Electronic books- OSLIS; Electronic books